Mechanism of resistance to phagocytosis and pulmonary persistence in mucoid Pseudomonas aeruginosa - Rowe, Warren J.; Lebman, Deborah A.; Ohman, Dennis E. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Pseudomonas aeruginosa is known for its ability to form biofilms, which are dependent on the production of exopolysaccharides. During chronic colonization of the airway and biofilm formation, P. aeruginosa converts to a mucoid phenotype, indicating production of the exopolysaccharide alginate. The mucoid phenotype promotes resistance to phagocytic killing, but the mechanism has not been established. Methods and Results To better understand the mechanism of phagocytic evasion conferred by alginate production, Human (THP-1) and murine (MH-S) macrophage cell lines were used to determine the effects of alginate production on macrophage binding, signaling and phagocytosis. Phagocytosis assays using mucoid clinical isolate FRD1 and its non-mucoid algD mutant showed that alginate production inhibited opsonic and non-opsonic phagocytosis, but exogenous alginate was not protective. Alginate caused a decrease in binding to murine macrophages. Blocking antibodies to CD11b and CD14 showed that these receptors were important for phagocytosis and were blocked by alginate. Furthermore, alginate production decreased the activation of signaling pathways required for phagocytosis. Mucoid and non-mucoid bacteria induced similar levels of MIP-2 from murine macrophages. Discussion This study demonstrated for the first time that alginate on the bacterial surface inhibits receptor-ligand interactions important for phagocytosis. Our data suggest that there is a selection for alginate conversion that blocks the earliest steps in phagocytosis, leading to persistence during chronic pulmonary infections.